The rural health initiative: Bridging gaps in healthcare access and grant-funded research in central Idaho - Monica Zigman Suchsland; Dillon van Rensburg; Kelly McGrath; Cody Wilkinson; Kimberly Johnson; Ashley Steinbruecker; James Probus; Allison Cole (Journal of Clinical and Translational Science)
Abstract